Seroprevalence of COVID-19 among health workers in the Kathmandu Valley, Nepal: a longitudinal cohort study (Nepal Medical College Journal, 2022)
Coronavirus Disease 2019 (COVID-19) burden, often underestimated by case-based incidence reports, can be accurately estimated by measuring the population that has developed antibodies following an infection. Here, we report the prevalence of COVID-19 antibodies among health workers in Kathmandu, Nepal. This seroepidemiology of COVID-19 was a longitudinal survey of hospital-based health workers working in 20 hospitals in the Kathmandu Valley. A total of 800 participants were chosen in December 2020 by a two-stage cluster-stratified random sampling method and administered a questionnaire eliciting COVID-19 related history. A blood sample was also obtained from the participants and tested for COVID-19 IgG antibodies using a Chemiluminescence Immunoassay (CLIA). We then used a probabilistic multilevel regression model with post-stratification to correct for test accuracy, the effect of hospital-based clustering, and to ensure representativeness. The final analytic sample included 800 participants; 522 (65.2%) of them were female, 372 (46%) were between ages 18-29, 287 (36%) were nurses. Of the total 800, 321 (40.1%) individuals tested positive for COVID-19 antibodies. Adjusted for test accuracy and health-worker population, the seroprevalence was 38.2% (95% Credible Interval (CrI) 29.26%–47.82%). Posterior predictive hospital-wise seroprevalence ranged between 38.1% (95% CrI 30.7.0%–44.1%) and 40.5% (95% CrI 34.7%–47.0%). Our study suggested that about two in five health workers in the Kathmandu Valley were seropositive against SARS-CoV-2 by December 2020; a substantial proportion of them did not have a documented infection.